Answer:
Part a)
Steve's expression is [tex]2(2x+5)^{2}-7[/tex]
For x=3, the expression is equal to [tex]235[/tex]
Part b)
Jasmine's expression is
[tex](3x^{2})+(25x)[/tex]
For x=2, the expression is equal to [tex]62[/tex]
Step-by-step explanation:
Part a)
Let
n-----> the first term
The expression is
[tex](n-7)[/tex]
[tex]n=2(2x+5)^{2}[/tex]
substitute
Steve's expression is
[tex]2(2x+5)^{2}-7[/tex]
Evaluate for x=3
[tex]2(2(3)+5)^{2}-7=242-7=235[/tex]
Part b)
Let
n-----> the first term
Jasmine's expression is
[tex](3x^{2})+(25x)[/tex]
Evaluate for x=2
[tex](3(2)^{2})+(25(2))=12+50=62[/tex]